Understanding Personality Disorders’ Traits Through Schema Modes and Temperament - Preliminary Study in Non-Clinical Population - Zaborowska, Julia (Przegląd Psychologiczny, 2024)
Objective: According to Schema Therapy (ST) theory, both temperament and schema modes play acritical role in an individual’s development and functioning. This study aimed to investigate how schema modes, as conceptualized in ST, and temperament, as defined by Reinforcement Sensitivity Theory (RST)—jointly contribute to the severity of personality disorder symptoms in the general population. Specifically, it how biological predispositions (i.e., temperament) and developed psychological patterns (i.e., schema modes) co-explain dysfunctional personality symptoms in a non-clinical sample. Based on theoretical frameworks and previous single-theory research, it was expected that these factors would show meaningful associations with the severity of personality pathology. Methods: Data were collected from 43 participants, aged 19–33 years, who completed three questionnaires: a preliminary adaptation of the Schema Mode Inventory (SMI) to assess the intensity of schema modes, the Reinforcement Sensitivity Theory Personality Questionnaire (RST–PQ) to measure temperamental system activity, and the Screening Personality Questionnaire (SCID–5–SPQ) to assess the severity of personality disorders’ symptoms. Partial least squares regression (PLSR) was conducted to analyze nine models corresponding to each personality disorder. Results: The analysis indicated that specific configurations of schema modes and temperamental systems were significant predictors of personality disorder symptoms in all models. The model for dependent personality disorder symptoms demonstrated the highest R² value, accounting for 62% of the variance in symptom severity. Conclusions: Preliminary findings highlight the significance of both acquired and innate factors in the expression of pathological personality symptoms in a non-clinical population. These results underscore the need for further validation and the integration of both perspectives into diagnostic and therapeutic approaches.